In vitro construction of the COQ metabolon unveils the molecular determinants of coenzyme Q biosynthesis - Callum R. Nicoll; Laura Alvigini; Andrea Gottinger; Domiziana Cecchini; Barbara Mannucci; Federica Corana; María Laura Mascotti; Andrea Mattevi (2024)
Metabolons are protein assemblies that perform a series of reactions in a metabolic pathway. However, the general importance and aptitude of metabolons for enzyme catalysis remain poorly understood. In animals, biosynthesis of coenzyme Q is currently attributed to ten different proteins, with COQ3, COQ4, COQ5, COQ6, COQ7 and COQ9 forming the iconic COQ metabolon. Yet several reaction steps conducted by the metabolon remain enigmatic. To elucidate the prerequisites for animal coenzyme Q biosynthesis, we sought to construct the entire metabolon in vitro. Here we show that this approach, rooted in ancestral sequence reconstruction, reveals the enzymes responsible for the uncharacterized steps and captures the biosynthetic pathway in vitro. We demonstrate that COQ8, a kinase, increases and streamlines coenzyme Q production. Our findings provide crucial insight into how biocatalytic efficiency is regulated and enhanced by these biosynthetic engines in the context of the cell.